Platelet activation following application of an Esmarch bandage and tourniquet in rabbits. - Yoshida, W. B.; Thomazini, I. A.; Carvalho, I.; Lastória, S.; Curi, P. R.; Maffei, F. H. (My University, 1989)
The present study evaluates platelet activation following application of an Esmarch bandage and a tourniquet, procedures commonly employed to provide a bloodless operative field during limb surgery. Platelet aggregation was increased in blood samples taken from rabbits 60 min after an Esmarch bandage was applied to one thigh and immediately released. When this treatment was combined with the application of a tourniquet for 60 min, a procedure which alone did not affect platelet aggregation, results were similar to those obtained following the Esmarch bandage alone. These data suggest that tissue compression produced by application of an Esmarch bandage, but not the ischemia derived from the tourniquet, produced platelet aggregation.